(untitled) (MAUSAM, 1983)
A single-level primitive equation model is used to predict the movement of monsoon depressions over the Arabian Sea and the Bay of Bengal. The data used are for the Monsoon Experiment-1979 (MONEX- 79). The model formulation is based on shallow water equations. The finite-differencing scheme is designed to conserve total energy and mass over the domain during the, course of integration. The initial input to the model is the subjectively analysed wind field from which geopotential field is derived through balance wind relation. Dynamic initiallzation,is used to balance the mass and wind fields consistent with the model equations. The movement of three depressions has been studied. The model is able to predict their movement to a limited degree of accuracy. The total energy IS conserved well during the course of integration.